The crystal structure of 1-methyl-2-nitro-1H-imidazole 3-oxide, C4H5N3O3 - Yuan Jun (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C4H5N3O3, monoclinic, P21/n (no. 14), a = 8.4556(2) Å, b = 7.0609(3) Å, c = 9.5928(4) Å, β = 90.12(2)°, V = 572.73(4) Å3, Z = 4, Rgt(F) = 0.0339, wRref(F2) = 0.0914, T = 140.0 K.